Female Monsters: Figuring Female Transgression in Jennifer's Body (2009) and The Witch (2013) - Aidatul Chusna; Shofi Mahmudah (Humaniora, 2018)
This paper aimed to examine the depiction of the monstrous feminine in two horror flms, 2009’s Jennifer’s Bodyand 2015’s The Witch, by investigating how horror flms confront transgression through the construction of woman as a monstrous fgure in the story. The theory of abjection proposed by Julia Kristeva and of the monstrous feminine by Barbara Creed were used in the analysis. The main data were taken from these two flms, focusing on the characterization and narrative aspects. It was found that the depiction of the monstrous feminine in both flms was through the use of monstrous acts and images. The way in which these flms constructed monstrosity indicates female transgression of patriarchal boundaries, specifcally on the issue of gender identity and religiosity. The transgression emphasizes that there is no absolute identity, and thus boundaries are disrupted due to this ﬂuid identity